Mitochondrial DNA variation in sudden cardiac death: a population-based study - Kytövuori L.; Junttila J.; Huikuri H.; Keinänen-Kiukaanniemi S.; Majamaa K.; Martikainen M. (Springer Verlag, 2022)
Cardiomyopathy and cardiac conduction defects are common manifestations of mitochondrial disease. Previous studies suggest that clinically asymptomatic individuals harbouring pathogenic mitochondrial DNA (mtDNA) mutations in the cardiac muscle may have sudden cardiac death (SCD) as the first manifestation of mitochondrial disease. We investigated the contribution of pathogenic mtDNA point mutations and mtDNA haplogroups in cardiac muscle in a cohort of 280 Finnish subjects that had died from non-ischaemic SCD with the median age of death at 59 years and in 537 population controls. We did not find any common or novel pathogenic mutations, but the frequency of haplogroup H1 was higher in the SCD subjects than that in 537 population controls (odds ratio: 1.76, confidence interval 95%: 1.02–3.04). We conclude that, at the population level, pathogenic point mutations in mtDNA do not contribute to non-ischaemic SCD, but natural variation may modify the risk.